Nanoadditives induced enhancement of the thermal properties of paraffin-based nanocomposites for thermal energy storage - Owolabi, A.L. (Elsevier Ltd, 2016)
Nanocomposites of a paraffin wax base containing various concentrations (0.5, 1.0, and 1.5Â wt.) of the aluminium, copper, zinc and iron nanoadditives were investigated experimentally and theoretically. The experimental results revealed that an increased weight percent of the additives, within the investigated range, enhanced the thermal properties for TES application. Adding 1.5Â wt. of Cu and Zn nanoparticles enhanced the thermal conductivity of the nanocomposite by 20.6 and 61.5, respectively. The thermal diffusivity was observed to increase proportionally as the thermal conductivity increases, whereas the specific heat decreases. The experimental results were compared with existing models, and they disagreed with the prediction results of the thermal conductivity values for all of the models in the literature. The Maxwell and Hamilton-Crosser models predicted the closest values to the experimental results; however, they underpredicted the thermal conductivity of the nanocomposite, whereas the values from the other models significantly overpredicted the thermal conductivity values. The collector efficiency performance was enhanced by 15.5 when integrated with PCM-TES. A further enhancement was reported when the collector system was integrated with nanocomposite-TES. The enhanced PCM nanocomposites exhibited improved thermal energy storage capability, mainly in solar/TES integrated applications. Â© 2016 Elsevier Ltd